50.9k views
4 votes
Can you guys please help me step by step ?2(2x-1)=6(x+2)

User Duemir
by
5.4k points

2 Answers

1 vote

Answer:

Explanation:

2(2x-1)=6(x+2) PEDMAS

4x-2=6x+12 subtract 4x from both sides

-2=2x+12 subtract 12

-14=2x divide by 2

x= -7

User Adrien BARRAL
by
5.6k points
2 votes

Answer:

x = -7

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Explanation:

Step 1: Define equation

2(2x - 1) = 6(x + 2)

Step 2: Solve for x

  1. Distribute: 4x - 2 = 6x + 12
  2. Subtract 4x on both sides: -2 = 2x + 12
  3. Subtract 12 on both sides: -14 = 2x
  4. Divide 2 on both sides: -7 = x
  5. Rewrite: x = -7

Step 3: Check

Plug in x to verify it's a solution.

  1. Substitute: 2(2(-7) - 1) = 6(-7 + 2)
  2. Multiply: 2(-14 - 1) = 6(-7 + 2)
  3. Subtract/Add: 2(-15) = 6(-5)
  4. Multiply: -30 = -30

Here we see that -30 does indeed equal -30.

∴ x = -7 is a solution of the equation.

User Ruslan Kuleshov
by
5.8k points